EVALUATION OF THE MANAGEMENT AND DISTRIBUTION OF ELECTION LOGISTICS IN THE 2020 REGIONAL HEAD ELECTIONS IN PALU CITY - Bonde, Merlina; Saharuddin Kaseng; Syamsuddin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to analyze the process of the Regional Head Election held in Palu City in 2020. The 2020 Regional Election process faced numerous issues, including delays in regulations issued by the Central Election Commission (KPU), which caused challenges for field implementers. The election logistics distributed by the Palu City Election Commission to polling stations (TPS) were not adequately allocated according to TPS needs. The lack of logistics at several TPS resulted in delayed voting, preventing the process from starting on time. This study aims to describe field facts using existing data and information, which will then be evaluated for future elections in Palu City. The research uses a descriptive approach with a qualitative method. The types of data used are primary and secondary data, collected through interviews. The study's findings reveal that during the distribution process of election logistics for the 2020 simultaneous Regional Head Elections in Palu City, several critical events occurred from the preparation to the implementation stages. Many regulations were unclear and impractical, making them difficult to understand and execute, particularly under pandemic conditions. While the Central Election Commission had issued a guideline titled the